Tetralogy of Fallot: T-shaped infundibulotomy for pulmonary valve-sparing procedure. (4th October 2021) - Leobon, Bertrand; Cousin, Grégoire; Hadeed, Khaled; Breinig, Sophie; Alacoque, Xavier; Berthomieu, Lionel; Karsenty, Clément
Abstract: This new and easily reproducible pulmonary valve-sparing technique for the correction of Tetralogy of Fallot is based on a conservative management of the native pulmonary valve to preserve its growth potential. From July 2015 to December 2019, 67 children presenting with a Tetralogy of Fallot were operated consecutively in a single centre using this technique in all cases. A T-shaped infundibulotomy is used to release the anterior pulmonary annulus from any muscular attachment. After myocardial resection and ventricular septal defect closure, an extensive commissurotomy is achieved. Finally, the right ventricular outflow tract remodelling is completed by a shield-shaped bovine patch with an oversized square superior edge, attached directly on the pulmonary valve annulus, with an effect of systolic traction. Sixty patients (89.5%) had a Tetralogy of Fallot repair with preservation of the pulmonary valve. To date, with a median follow-up of 38.2 [14–64] months, no patient has needed a surgical or interventional procedure for pulmonary valve stenosis or regurgitation, with low residual gradients. This procedure could provide a significant increase in native pulmonary valve preservation. Long-term studies are needed to assess pulmonary valve growth and the consequent reduction in surgical or interventional reoperations. Abstract : Tetralogy of Fallot (ToF) repair often leads to significant pulmonary valve insufficiency, with well-established long-term complications [1, 2].